Teaching a Child with Cochlear Implant to Read Words with Orthographic Difficulties - Cravo, Felipe Augusto Monteiro [UNESP]; Almeida-verdu, Ana Claudia Moreira [UNESP]; Lucchesi, Fernando Del Mando; Silva, Leandra Tabanez Do Nascimento; Moret, Adriane Lima Mortari (Sociedade Brasileira de Psicologia, 2019)
Considering the effects of reading on the accuracy of the speech of deaf and hard and hearing children and cochlear implants presented in the scientific literature, the main aim of this study was to evaluate the effects of Module 2 of the ALEPP software regarding teaching words with orthographic difficulties to a cochlear implanted child. The participant was a girl, had nine years of age, with profound bilateral and sensorineural hearing loss. The program aims to teach contingencies of the selection of printed words and syllables conditioned to dictated words and syllables of six different stimuli sets; each set contained 16 words, with a total of 96 teaching words and 64 control words. Probes of 160 words were interspersed with the teaching steps according to the multiple probe design. The participant learned to read the 96 taught words, controlled by the words’ minimal units. She presented maintenance of performance and reading generalization of the control words. The number of speech accuracy errors only decreased after the teaching intervention. The results replicated those of previous studies with orthographically easier words and future studies may explore the different types of training provided by the ALEPP and its effects on the accuracy of the speech of cochlear implanted children.

Considerando los efectos de la enseñanza de lectura sobre la precisión del habla en niños con deficiencia auditiva e implante coclear presentados en la literatura, el objetivo de este estudio fue verificar los efectos del Módulo 2 de ALEPP® sobre la enseñanza de lectura de palabras con dificultades ortográficas a una niña usuaria de implante coclear. La participante tenía nueve años, deficiencia auditiva profunda, bilateral y neurossensorial. El programa exposu a contingencias de enseñanza de selecciòn de palabras y silabas impresas condicionalmente a las palabras y silabas dictadas con seis conjuntos de estímulos; cada conjunto estaba compuesto por 16 palabras, totalizando 96 palabras de enseñanza; otras 64 palabras funcionaron como control. Las pruebas de las 160 palabras intercalaron la enseñanza de acuerdo con el delineamiento de múltiples sondas. La participante aprendió a leer las 96 palabras objetivo de enseñanza, con establecimiento de control por las unidades mínimas, mantenimiento de desempeño y generalización en la lectura de palabras control. Los errores en la precisión del habla disminuyeron sólo después de la inserción de la enseñanza. Los resultados replican estudios anteriores con palabras sin dificultades ortográficas y futuras investigaciones pueden explorar los efectos de los tipos de entrenamientos ofrecidos por el ALEPP® y sus efectos sobre la precisión del habla y el control por las unidades mínimas.

Considerando os efeitos do ensino de leitura sobre a precisão da fala de crianças com deficiência auditiva e implante coclear apresentados na literatura, o objetivo deste estudo foi verificar os efeitos do Módulo 2 do ALEPP® sobre a precisão da fala em leitura de palavras com dificuldades ortográficas a uma criança usuária de implante coclear. A participante tinha nove anos, com deficiência auditiva profunda, bilateral e sensorioneural. O programa expôs a contingências de ensino de seleção de palavras e sílabas impressas condicionalmente a palavras e sílabas ditadas com seis conjuntos de estímulos (ç, lh, ch, vLc, vNc e vRc); cada conjunto era composto por 16 palavras, totalizando 96 palavras de ensino; outras 64 palavras funcionaram como controle. Testes das 160 palavras intercalaram o ensino de acordo com o delineamento de múltiplas sondas. A participante aprendeu a ler as 96 palavras-alvo de ensino, com estabelecimento de controle pelas unidades mínimas alvo, manutenção de desempenho e generalização na leitura de palavras controle. Erros na precisão da fala diminuíram somente após o ensino. Os resultados replicam estudos anteriores com palavras simples e futuras investigações podem isolar os tipos de treino do ALEPP® e explorar seus efeitos sobre a precisão da fala e sobre o controle pelas unidades mínimas.
Enseñanza de Lectura de Palabras con Dificultades Ortográficas para Niña Usuaria con Implante Coclear
Ensino de Leitura de Palavras com Dificuldades Ortográficas para uma Criança com de Implante Coclear
Keywords: Reading teaching; speech accuracy; cochlear implant; Ensino de leitura; precisão da fala; implante coclear